Using Remote Communication Technology in Insulin Pump Training: A Feasibility Study. (March 2016) - Parks, Linda; Kim, Tae Youn
Purpose: This feasibility study was designed to examine if remote communication technology can be used in the technical training of an insulin pump in adults with diabetes who were familiar with insulin pump therapy. Methods: Surveys were emailed to 69 individuals who purchased an insulin pump and had been trained by the manufacturer's diabetes educators. In consultation with providers, participants were given the choice of receiving training in a face-to-face meeting or via remote communication technology. The survey consisted of 27 questions asking participants' characteristics, device proficiency, confidence, and their satisfaction with the insulin pump and the training method. Differences between the 2 groups were examined using bivariate analyses. Results: There were 17 participants in the remote group and 20 participants in the face-to-face group. Participants had a mean age of 40.9 ± 14.3 years, had diabetes for 24.3 ± 13.8 years, and used an insulin pump for 9.8 ± 4.9 years. The participants in both groups were not statistically different in age, diabetes history, years on insulin pump, device proficiency, confidence, or satisfaction with the training method. The remote group reported less graduate-level education ( P < .05) and higher satisfaction scores with the insulin pump training ( P < .05). Conclusion: Although this study has limitations associated with the small sample size and self-selection bias, the results suggest that remote communication technology may be an effective tool to provide technical training to adults who are familiar with insulin pump therapy. Additional research is required to determine the effectiveness of the remote insulin pump training.